2007
DOI: 10.1007/s10295-007-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of d-arabitol by a newly isolated Zygosaccharomyces rouxii

Abstract: A newly isolated Zygosaccharomyces rouxii NRRL 27,624 produced D-arabitol as the main metabolic product from glucose. In addition, it also produced ethanol and glycerol. The optimal conditions were temperature 30 degrees C, pH 5.0, 350 rpm, and 5% inoculum. The yeast produced 83.4 +/- 1.1 g D-arabitol from 175 +/- 1.1 g glucose per liter at pH 5.0, 30 degrees C, and 350 rpm in 240 h with a yield of 0.48 g/g glucose. It also produced D-arabitol from fructose, galactose, and mannose. The yeast produced D-arabito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Zakaria [24] reported that Candida famata R28 grew very well in the medium containing D-glucose as the sole carbon source and was able to produce D-arabitol as the single product of metabolism, but he did not present the concentration of this compound in fermentation broth. Saha et al [25] reported that Candida albicans, Candida pelliculosa and C. famata could produce D-arabitol from glucose, but usually incubation time was long and yields too small to be industrially acceptable. It may be concluded based on existing reports that Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…Zakaria [24] reported that Candida famata R28 grew very well in the medium containing D-glucose as the sole carbon source and was able to produce D-arabitol as the single product of metabolism, but he did not present the concentration of this compound in fermentation broth. Saha et al [25] reported that Candida albicans, Candida pelliculosa and C. famata could produce D-arabitol from glucose, but usually incubation time was long and yields too small to be industrially acceptable. It may be concluded based on existing reports that Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…Candida entomeae and Pichia guillermondii were known to produce xylitol and arabitol from hydrolysates containing xylose and arabinose (Saha and Bothast 1996). Saha et al (2007) showed that Zygosaccharomyces rouxii NRRL 27624 is capable of producing arabitol and ethanol from glucose but could not metabolize arabinose, which also is a prime component of hemicelluloses.…”
Section: Introductionmentioning
confidence: 99%
“…D-Arabitol is a key compound selected as one of the 12 potent building-block chemicals for biorefinery by the Department of Energy in the United States [12]. Despite a number of studies on the production of D-arabitol from D-glucose utilizing osmophilic yeast Zygosaccharomyces rouxii NRRL Y-27624 [13], Debaryomuces hansenii [9], Candida famata R28 [14], C. parapsilosis FERM P-18006 [15], or Metschnikowia reukaufii AJ14587 [16], there are remarkably few reports available on the production of D-arabitol from lactose.…”
Section: Introductionmentioning
confidence: 99%